2019
DOI: 10.1038/s41598-019-45859-9
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 mediated generation of an ovine model for infantile neuronal ceroid lipofuscinosis (CLN1 disease)

Abstract: The neuronal ceroid lipofuscinoses (NCLs) are a group of devastating monogenetic lysosomal disorders that affect children and young adults with no cure or effective treatment currently available. One of the more severe infantile forms of the disease (INCL or CLN1 disease) is due to mutations in the palmitoyl-protein thioesterase 1 ( PPT1 ) gene and severely reduces the child’s lifespan to approximately 9 years of age. In order to better translate the human condition than is possible in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 43 publications
(58 reference statements)
1
59
0
Order By: Relevance
“…If an incompatible PAM or target site sequence is introduced into the genome via the knock-in, the sgRNA-Cas9 complex can no longer bind to the target site, and no further edits can be made. The use of ssODN to induce knock-in or to improve knockout efficiency has been reported recently in ruminant species (sheep: [15,16]; goats: [17]; cows [27]).…”
Section: The Repair Templatementioning
confidence: 99%
See 3 more Smart Citations
“…If an incompatible PAM or target site sequence is introduced into the genome via the knock-in, the sgRNA-Cas9 complex can no longer bind to the target site, and no further edits can be made. The use of ssODN to induce knock-in or to improve knockout efficiency has been reported recently in ruminant species (sheep: [15,16]; goats: [17]; cows [27]).…”
Section: The Repair Templatementioning
confidence: 99%
“…When SCNT is mastered by the laboratory, the low efficient rate will be compensated with most of the healthy born animals carrying the desired mutation. Genome editing mediated by SCNT is applied by some laboratories in some kind of projects (e.g., multiplex editing), but the high efficiency of CRISPR after direct microinjection into zygotes has allowed an easier approach (sheep: [6,7,15,16]; goats: [9,17]; pigs: [11,13]). All together, these reports showed that with CRISPR it is possible to perform direct microinjection into the zygote of different species, with minimum effects on developmental competence and pregnancy rates, high newborn survival rate, and high editing rate with acceptable homozygous proportion.…”
Section: Embryo Manipulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although reported in other species [17][18][19] , current literature is scarce for CRISPR assisted ssODN-mediated homologous recombination in ruminant species (i.e., sheep, goats and cattle). Recently, Williams et al 5 reported for the first time the effectiveness of this tool to induce a point mutation in sheep, and Eaton et al 20 described the generation of homozygotes lambs by the insertion of a human mutation into the orthologous sheep locus. In the current study, we successfully generated both indel mutations and HDR-mediated KI using the ssODN strategy in sheep.…”
Section: Discussionmentioning
confidence: 99%